2010
DOI: 10.1051/0004-6361/201015230
|View full text |Cite
|
Sign up to set email alerts
|

X-ray observations of sub-mm LABOCA galaxies in the eCDFS

Abstract: We explore the X-ray properties of the 126 sub-mm galaxies (SMGs) of the LABOCA survey in the CDFS and the eCDFS regions. SMGs are believed to experience massive episodes of star formation. Our goal is to examine whether star formation coexists with AGN activity, determine the fraction of highly obscured AGN, and finally to obtain an idea of the dominant power mechanism in these sources. Using Spitzer and radio arcsecond positions for the SMGs, we find 14 sources with significant X-ray detections. For most of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 78 publications
5
35
1
Order By: Relevance
“…The SMGs not hosting AGN were consistent with X-ray emission from star-formation and HMXBs. Further X-ray analysis of SMGs estimate AGN fractions of 20-29(±7)% (Laird et al, 2010), <26±9% (Georgantopoulos et al, 2011), 14-28% and 17( +16 −6 )% . The Wang et al (2013a) work is of particular note since its sample is the ∼100 ALMA-confirmed 870µm-selected sources in CDFS with unambiguous counterparts, enabling effectively more precise measurements in both X-ray and FIR.…”
Section: Agn Contentmentioning
confidence: 98%
See 1 more Smart Citation
“…The SMGs not hosting AGN were consistent with X-ray emission from star-formation and HMXBs. Further X-ray analysis of SMGs estimate AGN fractions of 20-29(±7)% (Laird et al, 2010), <26±9% (Georgantopoulos et al, 2011), 14-28% and 17( +16 −6 )% . The Wang et al (2013a) work is of particular note since its sample is the ∼100 ALMA-confirmed 870µm-selected sources in CDFS with unambiguous counterparts, enabling effectively more precise measurements in both X-ray and FIR.…”
Section: Agn Contentmentioning
confidence: 98%
“…The X-ray properties of DSFGs have been studied in detail over the past decade, in particular for 850-870µm-selected SMGs (Fabian et al, 2000;Alexander et al, 2005a,b;Pope et al, 2006;Laird et al, 2010;Lutz et al, 2010;Georgantopoulos et al, 2011;Gilli et al, 2011;Hill & Shanks, 2011;Bielby et al, 2012;Johnson et al, 2013;Wang et al, 2013b). Unfortunately, all of these studies are limited by small number statistics (N sources < 100) cause by very time-intensive, deep X-ray observations which are required to disentangle X-ray emission dominated by AGN Figure 27: A summary of X-ray observations of ∼850µm-selected SMGs.…”
Section: Agn Contentmentioning
confidence: 99%
“…In particular instances of quite large gravitational amplification we can even get estimates of the BH mass. These observations should be complemented by X-ray observations, which for magnification 10 will allow us to get a detailed view of the nuclear emission even for highly obscured and quite low luminosity objects (Matt et al 2004;Georgantopoulos et al 2011). The predicted intrinsic X-ray luminosity for typical lensed galaxies exceeds L X 10 42 erg s −1 ; the magnification by factors 10 makes them easily detectable in pointed observations up to z 3 with Chandra and the next generation of X-ray instruments.…”
Section: The Reservoirmentioning
confidence: 99%
“…The FIR/submm selection elicits galaxies with bolometric luminosity associated to star formation larger than the AGN bolometric luminosity (L FIR /L AGN 1; see Georgantopoulos et al 2011;Laird et al 2010;Rafferty et al 2011;). The few objects that exhibit a ratio L FIR /L AGN ∼ 1 have a large X-ray power L X 3 × 10 44 erg s −1 and large luminosity in the Hα line (Alexander et al 2008).…”
Section: The Relationship Between Star Formation and Bh Growth: Data mentioning
confidence: 99%
See 1 more Smart Citation